Targeted analysis of protein termini. - Dormeyer, W; Mohammed, S; Breukelen, B; Krijgsveld, J; Heck, A (2007)
We describe a targeted analysis of protein isoforms by selective enrichment and identification of in vivo acetylated protein N-termini and protein C-termini. Our method allows the characterization of these protein termini regardless of their annotation in protein databases and requires no chemical derivatization. Using an iterative database search strategy that takes account of the enrichment protocol, 263 IPI annotated and 87 unpredicted acetylated N-termini were identified in the crude membrane fraction of human embryonic carcinoma cells. The N-acetylated peptides conform to the reported criteria for in vivo modification. In addition, 168 IPI annotated and 193 unpredicted C-termini were identified. Additionally, and for the first time, we also report on in vivo N-terminal propionylation. The significant number of unknown protein N- and C-termini suggests a high degree of novel transcription independent of annotated gene boundaries and/or specific protein processing. Biological relevance of several of these unpredicted protein termini could be curated from the literature, adding further weight to the argument to go beyond routine database search strategies. Our method will improve the correct annotation of genes and proteins in databases.